Pengaruh Intellectual Capital Terhadap Kinerja Keuangan Perusahaan Dan Dampak Pada Harga Wajar Saham( Studi Kasus pada Perusahaan Real Estate yang Terdaftar pada Bursa Efek Singapura ) - Prasetyaningtiyas, Pungky, Dra. Wafiatun Mukharomah, MM (2017)
This study aims to determine the effect of intellectual capital on the financial performance of real-estate industry. The hypothesis of this study is that there is a positive effect of intellectual capital on the financial performance and its impact on the stock price is reasonable. Variable intellectual capital is human capital, structural capital and relational capital. Variable financial performance using proxies is Return On Equity (ROE), Earning Per Share (EPS) and Return On Investment (ROI). This study examines the real-estate company listed on the Singapore Stock Exchange in 2014-2016. This study uses the classical assumption test and partial test. These results indicate that intellectual capital (MVAIC) has positive and significant impact on the financial performance and has a positive impact on the company's stock price is reasonable.